Faktor-Faktor Yang Memengaruhi Continuance Intention to Use Bank Digital X Melalui Satisfaction - Clarisa, Imelda Bella; Yohana, Corry; Parlyna, Ryna (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to explore the impact of perceived usefulness and confirmation on continuance intention to use with satisfaction as a mediating variable among users of Bank X’s application. A quantitative approach was applied through a survey method with online questionnaire distribution. Data was obtained from 150 respondents who were active Bank X users, aged between 18 and 45 years old, residing in DKI Jakarta, and had the intention to continue using the Bank X application. Data analysis was performed using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The research findings revealed that perceived usefulness had a positive and significant effect on satisfaction. Confirmation also showed a positive and significant effect on satisfaction. In addition, satisfaction had a positive and significant effect on continuance intention to use. Perceived usefulness did not show a direct effect on continuance intention to use. However, confirmation had a positive and significant effect on continuance intention to use. Furthermore, perceived usefulness had a positive and significant effect on continuance intention to use through the mediation of satisfaction. Confirmation also had a positive and significant effect on continuance intention to use through the mediation of satisfaction. Finally, confirmation showed a positive and significant effect on perceived usefulness.